A randomised controlled multimodal intervention trial in patients with ischaemic stroke in Shandong, China: design and rationale. (December 2017) - Bai, Bo; Yan, Zhongrui; Hao, Yanlei; Zhang, Zuoji; Li, Gongying; Dekker, Joost; Qiu, Chengxuan
Abstract: Background: Stroke is the leading cause of death and disability in China and has conferred a huge economic and societal burden. The effectiveness of primary prevention of stroke by targeting major vascular or cardiometabolic risk factors (eg, smoking, hypertension, diabetes) has been well established. This study aims to investigate whether a personalised, multimodal, multilevel intervention programme is effective in modifying unhealthy lifestyle and improving control of major cardiometabolic risk factors in patients with ischaemic stroke, and thus in reducing the risk of recurrent stroke and associated complications (functional disability, cognitive impairment). Methods: This is a single-blind randomised controlled intervention study. Participants are recruited from two tertiary hospitals in Shandong, China. The inclusion criteria are first-ever ischaemic stroke or transient ischaemic attacks, age 40 years or older, and no loss of consciousness. Using local randomisation at participating hospitals, all eligible patients are randomly assigned (1:1), according to random number tables, to either the control group or the intervention group. Study participants but not investigators are blind to the intervention assignment. Patients in the control group receive standard care and treatment according to current guidelines, and those in the intervention group receive an additional personalised multilevel intervention procedure that consists of motivational interviewing for behavioural change (smoking, alcohol use, and medical adherence), dietary advice, and regular monitor of major cardiometabolic risk factors (high blood pressure, high serum cholesterol, and high blood glucose). Participants are being followed up every 6 months for up to 2 years. The primary outcomes are recurrent stroke, functional ability (at year 1), and cognitive performance (at year 2). The secondary outcomes are survival, quality of life, and depression. The protocols of this study were reviewed and approved by the Ethics Committee at Jining Medical University, Shandong, China. Written informed consent was obtained from participants or from health care proxies (next of kin). This trial is registered with the Chinese Clinical Trial Registry, number ChiCTR-IOR-16007741. Findings: The baseline recruitment procedure was tested to be feasible in the pilot study, with minor modifications. From Oct 15, 2015, to Dec 31, 2016, a total of 2000 patients (aged 40–92 years; 37% women) were recruited; of these, 999 patients were randomly assigned to the control group and 1001 to the intervention group. The intervention and follow-up assessments of participants are ongoing. Interpretation: This study will hopefully demonstrate the feasibility to implement a personalised, multimodal, multilevel intervention programme in patients with ischaemic stroke and TIAs. Findings from this study are expected to help improve secondary prevention of stroke and complications. Funding: Jining No. 1 People's Hospital, the Affiliated Hospital of Shandong Jining Medical University, and the Foreign Expert Program of the State Administration of Foreign Experts Affairs of China (20153500002).